THE RISE OF E-COMMERCE IN CENTRAL ASIA: A COMPARATIVE STUDY ON UZBEKISTAN'S E-COMMERCE LANDSCAPE COMPARED TO OTHER COUNTRIES IN THE REGION. (International conference on multidisciplinary science, 2024)
The purpose of the article is an objective assessment of the state of electronic commerce in the Central Asian region, on the basis of which the identification of urgent problems that impede the expansion of online commerce in Uzbekistan in the context of a serious transformation in the digital space. The development of networks of modern highly efficient forms and methods of trade leads to its transformation into a modern service industry. In particular, these are small forms of trade: convenience stores or retail outlets at gas stations, discounters.